Genome sequencing and biodegradation characteristics of the n-butyl benzyl phthalate degrading bacterium-Rhodococcus sp. HS-D2. (March 2018) - Zhang, Yunze; Chen, Huxing; Liu, Jiamei; Geng, Ge; Liu, Deli; Geng, Hui; Xiong, Li
Abstract: The n -butyl benzyl phthalate (BBP) is an environmental pollutant used extensively in the manufacturing of plastics. For the bioremediation of phthalic acid ester pollutants in water, sediment, and soil, a BBP degrading bacterium Rhodococcus sp. HS-D2 was isolated from contaminated river sediment and characterized. The HS-D2 strain is capable of utilizing BBP as the sole source of carbon. A shaken culture containing 500 mgL −1 of BBP produced complete degradation in 96 h. To study the metabolic characteristics and potential strategies for enhancing the biodegradation rates of BBP, a genome-scale metabolic model (GEM) of Rhodococcus sp. iYZ1601 was reconstructed based on the genome sequence of strain HS-D2. It included several sequential transporters and hydrolases were involved in the biodegradation process of BBP. Monoethylhexylphthalate (MEHP) and phthalic acid ester (PAE) hydrolases were confirmed as the key enzymes in phthalate degradation. The MEHP and PAE hydrolases catalyzed the conversion of BBP to butanal, phenylcarbinol, and phthalate as verified by HPLC analysis. The growth rate of HS-D2 and BBP consumption rate were analyzed in silico simulation, and were found to be consistent with the rates of HS-D2 growth and BBP consumption the in vitro experiment. In summary, Rhodococcus sp. HS-D2 biodegrades BBP, but the metabolic pathway of this bacterium needs further exploration to improve the biodegradation efficiency. Highlights: The genome of Rhodococcus sp. has been sequenced and key gene that associate with BBPs degradations was identified. BBP biodegradation was investigated by in vitro and in silicon. First report of characterizing pht and pae gene cluster in Rhodococcus sp.